Coated seeds with germination time controlled

The vinyl ether copolymer-coated seeds address the challenge of inconsistent germination timing by controlling the peeling of the coating based on temperature, enabling advanced sowing and uniform plant growth.

JP2025008202AActive Publication Date: 2025-01-20NAT UNIV CORP HOKKAIDO NAT UNIV ORG +1

Patent Information

Application Number
JP2023110159
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-20
Estimated Expiration
2043-07-04

AI Technical Summary

Technical Problem

Existing seed germination technologies struggle to ensure uniform and appropriate germination timing across varying soil conditions, leading to inconsistent growth and potential seed loss due to unsuitable weather conditions.

Method used

A coated seed with a vinyl ether copolymer coating that softens and peels off at a predetermined temperature, inhibiting water absorption until conditions are suitable for germination, ensuring seed viability and controlled germination timing.

Benefits of technology

The coated seeds allow for sowing in advance of the typical season, maintaining seed viability and ensuring germination at optimal growth periods, preventing freezing and withering, and promoting uniform plant growth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008202000013
    Figure 2025008202000013
  • Figure 2025008202000014
    Figure 2025008202000014
  • Figure 2025008202000015
    Figure 2025008202000015
Patent Text Reader

Abstract

To provide a coated seed capable of contributing to dispersion of work periods by advancing a sowing period to autumn or winter from a conventional cultivation system of sowing in spring.SOLUTION: There is provided a coated seed that makes it possible to suppress germination until an appropriate time while maintaining seed viability by coating the seed with a coating material that can inhibit water absorption, which triggers seed germination, until a temperature is suitable for germination and can be peeled off from the seed at a temperature that allows for growth (for example, a hydrophobic coating material containing a vinyl ether copolymer consisting of repeating units of the following formula (1), where R1 represents an alkyl group having 3 to 10 carbon atoms, and R2 represents a cyclic hydrocarbon group whose basic skeleton is an alicyclic group having 10 to 15 carbon atoms).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to coated seeds that can ensure good growth by suppressing germination until an appropriate time while maintaining seed viability when the sowing time is brought forward and the seeds are allowed to overwinter in farm fields in order to spread out agricultural work periods, mainly in cold regions. [Background technology]

[0002] In Hokkaido, sugar beets are a staple crop for field farming. To ensure a stable yield, they are cultivated by sowing seeds in paper tubes filled with soil, raising the seedlings for a certain period, and then transplanting them. On the other hand, in recent years, direct seeding of sugar beets has been expanding in order to reduce the labor required for raising seedlings and to cut costs, which increases with the expansion of the cultivated area per farm. Although direct seeding eliminates the need for raising seedlings, there is a problem of labor shortages, as the sowing period overlaps with the work period for other crops. In addition, if bad weather in early spring restricts the access of agricultural machinery to the fields, the sowing period may be delayed, and there is a risk that the crop will not have enough time to grow.

[0003] One method for ensuring the growing period of crops is to advance the sowing time. However, in cold regions, direct sowing can usually be started after snow melts or freeze-thaws in the field, and the period when sowing can be advanced is limited, so this does not provide a fundamental solution. As a solution to this problem, a technique is known in which directly sown seeds are allowed to germinate at any time, for example, by sowing in the autumn of the previous year before snowfall, so that the seeds overwinter in the field and germinate in early spring. Patent Document 1 discloses a technique for delaying the germination of seeds for a certain period of time by sealingly covering the outer periphery of the seeds with a biodegradable plastic and blocking the seeds from outside air and water for a certain period of time. Patent Document 2 discloses rice seeds that are sown in autumn with the aim of germinating in early spring, which are coated with a pinhole-free coating to impart hydrophobicity to the rice seeds so that they do not wither and die due to absorbing water in the field during the winter season, which is unsuitable for growth, and which are coated with hydrophobic polybutadiene having a number-average molecular weight of 400 to 1000 and a viscosity at 20°C of 100 to 500 centipoise in order to control the duration of this hydrophobicity. Patent Document 3 discloses a technology for a greening method using sowing seeds on slopes and the like, in which seeds are coated with an organic synthetic resin that contains a biodegradable resin, thereby blocking at least one of the factors that cause seed germination - oxygen, water, and temperature - for a certain period of time, thereby enabling sowing to be carried out even during periods when sowing is not suitable, by freely controlling seed germination or the germination time. This technology inhibits seed germination for a certain period of time. Patent Document 4 discloses a technique in which seeds having a moisture content in the range of 0 to 20% by weight are coated with a water-insoluble polyethylene polymer on the surface in order to maintain seed viability and inhibit germination until the appropriate time when the sowing time is arbitrarily brought forward from the start of cultivation. Patent Document 5 discloses a technique for greening herbaceous plants on newly formed ground surfaces due to civil engineering works, such as road slopes, lake / river slopes, etc., in which seeds are coated with a coating agent containing a biodegradable resin that is degraded and broken down by microorganisms in the soil so that the coating breaks down at a preset time after sowing, allowing the seeds to germinate and grow. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 8-21 [Patent Document 2] Special Publication No. 61-033523 [Patent Document 3] Japanese Patent Application Publication No. 8-256590 [Patent Document 4] JP 2017-35043 A [Patent Document 5] Japanese Patent Application Publication No. 8-149907 [Non-patent literature]

[0005] [Non-Patent Document 1] Namikoshi, T., Hashimoto, T., Urushisaki, M., Synthesis of poly(vinylether) plastics for optical use by Cationic copolymerization of tricyclodecyl vinyl ether with n-butyl vinyl ether, Journal of PolymerScience, Part a: Polymer Chemistry, 45(18), 4389-4393(2007) Summary of the Invention [Problem to be solved by the invention]

[0006] However, the technologies disclosed in Patent Documents 1 and 3 depend on the decomposition action of the coating layer (biodegradable resin) by microorganisms for the initiation of seed germination. If soil conditions are not constant depending on the area of ​​the field where the seeds are sown, and if there is a bias in the decomposition activity due to, for example, the population density of microorganisms or temperature conditions, there will be differences in the start of germination depending on the area of ​​the field, which may result in a greater difference in subsequent growth. The technology disclosed in Patent Document 2 was originally developed to solve the problem that rice seeds die when they are left in a state where they absorb moisture from the field during the winter period when growth is unsuitable, resulting in a decrease in the overall germination rate. It is not a technology intended to adjust the coating so that the seeds will germinate when the soil environment becomes suitable for germination. The technology disclosed in Patent Document 4 aims to suppress germination while maintaining seed viability by coating the surface of the seed with a coating containing an olefin-based polymer, which is a water-insoluble resin. The period of germination suppression depends on the composition of the coating and the coating content relative to the seed, and is not a technology intended to adjust the coating to peel off from the seed at a time when the soil environment is suitable for germination. Therefore, there is room for improvement in terms of ensuring good growth by germinating the seeds at the appropriate growth period. The technology disclosed in Patent Document 5 is a technology in which germination is only possible through the deterioration and breakdown of the biodegradable resin, and germination is suppressed for a certain period (3 to 6 months) after sowing, even if germination conditions such as temperature are appropriate. As described above, with the conventional techniques, it is difficult to ensure good growth by inhibiting germination until the appropriate growth period and then allowing germination under any temperature conditions.

[0007] The present invention has been made to solve the above-mentioned problems, and aims to provide a technology that can inhibit seed germination until the soil environment becomes suitable for germination, and can cause the seeds to germinate at the appropriate timing for growth, such as when temperature is reached. [Means for solving the problem]

[0008] The present invention relates to the following [1] to [5]. [1] A coated seed having a coating layer containing a vinyl ether copolymer on a surface of the seed, The vinyl ether copolymer is characterized in that the softening temperature, as defined by the following conditions, is 0.5°C or higher and the Tg is -35°C to 13°C. Coated seeds. <Softening temperature> The vinyl ether copolymer is filled into an aluminum pan (φ5.8 mm × height 1.5 mm), A roughly Y-shaped stainless steel rod (weight 0.21 g, total length of stainless steel rod 2.1 cm, length of handle 0.9 cm, bottom of handle 1.0 mm x 0.7 mm (roughly rectangular), length from crotch of branch to top of branch 1.2 cm, thickness of branch 0.7 mm, distance between tops of branch 0.85 cm) having a cylindrical handle and a branch at its tip that spreads out in two directions and has a flat top surface was inserted into the center of the copolymer with the branch pointing upward and the stainless steel rod was placed in contact with the bottom of the aluminum pan, and the temperature was raised from -20°C. The surface temperature of the copolymer measured with an infrared thermometer at the moment when the stainless steel rod falls completely is taken as the softening temperature. [2] The vinyl ether copolymer has a viscosity of 30 to 300 Pa s at 25°C and a number average molecular weight of 800 to 15,000. [1] The coated seed according to the present invention. [3] The coated seed according to [2], wherein the vinyl ether copolymer has a molecular weight distribution (Mn / Mw) of 2.0 or less. [4] The coated seed according to any one of [1] to [3], wherein the vinyl ether copolymer comprises a repeating unit represented by the following formula (1): [ka] (In formula (1), R1 represents an alkyl group having 3 to 10 carbon atoms; R2 represents a cyclic hydrocarbon group having an alicyclic group having 10 to 15 carbon atoms as a basic skeleton, p represents an integer of 3 to 95, q represents an integer of 2 to 38, and p and q satisfy p:q=5.8:4.2-7.2:2.8; m is the number of alkylene groups and is an integer of 0 or 1. [5] R1 is at least one group selected from the group consisting of an n-propyl group, an n-butyl group, an n-pentyl group, an n-hexyl group, an n-heptyl group, an n-octyl group, an n-nonyl group, an n-decyl group, an isopropyl group, an isobutyl group, a t-butyl group, an isopentyl group, a neopentyl group, an isohexyl group, an isoheptyl group, an isooctyl group, a 2-ethylhexyl group, an isononyl group, and an isodecyl group; The R2 is at least one group selected from the group consisting of groups represented by the following formulas (2) to (6): [4] The coated seed according to the present invention. [ka] (In the formula, * represents a bond.) Effect of the Invention

[0009] The coated seeds of the present invention enable the suppression of germination until an appropriate time while maintaining the viability of the seeds when the sowing time is brought forward from the conventional cultivation system of sowing in spring to sowing in autumn or winter in order to spread out the work period. For this purpose, the seeds are coated with a hydrophobic polymer that inhibits the seeds from absorbing water until the temperature reaches a suitable temperature for germination, so that even when the seeds are wintered in a field, frost death caused by the seeds absorbing moisture from the surroundings and freezing, and death of the plant body caused by germination in winter, which is a harsh condition for survival, can be prevented. In addition, the coating layer peels off from the seeds at a temperature suitable for growth, making it possible to germinate at the optimum growth period and ensure good growth of the plant thereafter. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a graph showing theoretical values ​​of Tg according to the Fox formula for copolymers having different composition ratios of n-butyl vinyl ether (NBVE) and tricyclodecane vinyl ether (TCDVE). [Diagram 2] FIG. 2 is a schematic diagram of the measurement of the softening temperature. [Diagram 3] FIG. 3 is a diagram showing the appearance of coated seeds (sugar beet seeds) before and after the peeling test. [Figure 4] FIG. 4 shows the schedules (1) to (3) of the germination test. [Diagram 5] FIG. 5 shows the germination of coated seeds (sugar beet seeds) subjected to a germination test according to schedule (2). [Figure 6] FIG. 6 shows the coating material found in the soil after the germination test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] (Coating material) The coating material used in the coated seed of the present invention is made of a polymer that has the effect of inhibiting water absorption by the coated seed until a certain temperature condition is reached. In other words, the coating material is a material that does not dissolve or disintegrate due to moisture, that is, a hydrophobic material (also called a hydrophobic polymer), and by maintaining a solidified state until a certain temperature is reached, it has the effect of preventing water from passing through the coating layer and penetrating into the seed. In this specification, the term "hydrophobic polymer" refers to a polymer that has low affinity for water. Taste.

[0012] (Softening temperature) The water absorption that triggers germination occurs when the coating layer made of the above-mentioned coating material that covers the seed softens at a certain temperature and peeling from the seed proceeds. In the present invention, the temperature at which the coating layer softens, that is, the temperature at which the solidified coating material has fluidity and becomes liquid, and peeling of the coating layer that covers the seed starts and proceeds, is defined as the "softening temperature." The softening temperature is the temperature that triggers peeling of the coating layer from the seed at a certain temperature, and can be used as an indicator of the temperature conditions that initiate germination, but in the present application it is used as a different concept from the optimum temperature for seed germination. The appropriate softening temperature according to the present invention is a temperature at which the coated seeds do not germinate during the severe cold season but rather germinate at a temperature suitable for germination in early spring, and must be at least 0.5° C. or higher. Although it also depends on the cold resistance of the germinating seedlings, in order to prevent growth stagnation and / or a decrease in survival rate due to exposure to cold air after germination, the temperature is preferably 3° C. or higher, more preferably 4° C. or higher, and even more preferably 5° C. or higher. The softening temperature can generally be measured by the method described in JIS K 7206 A50, but in the present invention, the temperature measured by the following method is regarded as the softening temperature. First, fill an aluminum pan (e.g., a crimp cell for DSC measurement) (φ5.8 mm×height 1.5 mm) with a coating material (polymer). If necessary, heat the polymer and fill the aluminum pan in a molten state. At this time, fill the aluminum pan with the polymer until it is leveled to the top edge. Then, place the aluminum pan on a temperature control unit set at −20° C., and pierce a roughly Y-shaped stainless steel rod into the center of the polymer in the aluminum pan so that it is in contact with the bottom of the aluminum pan, and leave the stainless steel rod standing upright. The roughly Y-shaped stainless steel rod used here weighs 0.21 g, has a total length of 2.1 cm, a handle length of 0.9 cm, a bottom surface of the handle: 1.0 mm×0.7 mm (roughly rectangular), a length from the crotch of the branched part to the top surface of the branched part of 1.2 cm, a thickness of the branched part of 0.7 mm, and a distance between the top surfaces of the branched parts of 0.85 cm. The branched parts are pierced and erected into the polymer so that they face upward. Next, the temperature is gradually increased from -20°C, and the surface temperature of the polymer in the aluminum pan at the moment when the stainless steel rod falls completely (as if the entire stainless steel rod is in contact with the polymer) is measured with an infrared thermometer, and this surface temperature is taken as the softening temperature.

[0013] (viscosity, number average molecular weight) In the coated seed of the present invention, setting the softening temperature is important as a main factor for controlling peeling of the coating layer from the seed, but setting the viscosity and number average molecular weight of the coating material can also be considered as secondary factors. For example, in order for the coating layer to peel off from the seeds, it is desirable for the coating material to have an appropriate viscosity in a softened state. That is, even if the coating material (polymer) reaches the glass transition temperature (Tg) described below, if the viscosity is high, the fluidity will be low, which may hinder the coating material from peeling off from the seeds. In the present invention, the viscosity at 25° C. can be used as an index of the viscosity at which the softened coating layer can be peeled off from the seed. Specifically, the viscosity of the coating material (polymer) may be 30 to 300 Pa s (a value measured with a vibration type viscometer at 25° C.), preferably 35 to 250 Pa s, and more preferably 38 to 200 Pa s. Generally, the viscosity of a polymer increases as the molecular weight of the polymer increases. Therefore, in order for the coating material to have the appropriate viscosity, the number average molecular weight (Mn) of the polymer that is the coating material is, for example, preferably 800 to 15,000, more preferably 1,000 to 14,000, and even more preferably 1,200 to 13,000. If the number average molecular weight (Mn) is 18,000 or more, the viscosity increases, and there is a risk that it will be difficult for the coating layer to peel off from the seeds under temperature conditions that allow germination. In other words, Generally, if the viscosity is reduced by decreasing the molecular weight, it is possible to control the temperature difference between Tg and softening temperature to a small value, and if the viscosity is increased by increasing the molecular weight, it is possible to control the temperature difference between Tg and softening temperature to a large value. Thus, one method of adjusting the viscosity of the coating material is to control the molecular weight of the polymer, and for example, by using living cationic polymerization, which allows control of the molecular weight during polymer preparation, molecular weight control can be achieved. That is, the polymer of the coating material according to the present invention can be a living cationic polymer. Of course, when preparing the polymer, commonly used polymerization methods such as anionic polymerization, living anionic polymerization, cationic polymerization, free radical polymerization, and living radical polymerization can be used. Furthermore, the coating material (polymer) according to the present invention preferably has a molecular weight distribution (Mw / Mn) of 2.0 or less, for example, 1.5 or less, or preferably 1.2 or less. The number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) may be values ​​calculated in terms of polystyrene by gel permeation chromatography (GPC).

[0014] (glass transition temperature) The glass transition temperature (Tg) is the freezing temperature of the micro-Brownian motion of the polymer main chain, i.e., the temperature at which the coating material starts to change from a glassy state to a viscous state, and is a physical property that serves as an index of the ease of softening of the polymer. In the present invention, it is assumed that the coating material passes through a released state (viscous state) from a solidified state (frozen state) as a preliminary stage before reaching a "softened" state (where peeling of the coating layer progresses). In other words, for the solidified coating material (polymer) to soften and peel off from the seed, it is necessary that at least the polymer of the coating material reaches the glass transition temperature and transitions from a frozen state to a viscous state. From this viewpoint, in the present invention, when the glass transition temperature (Tg) of the polymer, which is the coating material, is taken into consideration, the lower limit of the glass transition temperature (Tg) should be at least -35°C or higher, preferably -10°C or higher, more preferably -3°C or higher, and even more preferably 0°C or higher. From the viewpoint of proceeding with peeling at a temperature suitable for germination in early spring when the temperature has risen, the upper limit of Tg should be 10°C or lower, preferably 7°C or lower, and more preferably 5°C or lower. In addition, in consideration of avoiding the risk of frost damage, the upper limit of Tg can be determined in consideration of the temperature of the sowing environment, taking into account that sugar beet seedlings that have just germinated have low resistance to frost damage. For example, when the goal is to germinate at a time when the underground temperature reaches 10 to 15°C, such as early May in the Tokachi region of Hokkaido, the upper limit of Tg can be set to 13°C.

[0015] The glass transition temperature (θ) of a copolymer composed of two or more monomers can be theoretically calculated according to a calculation formula. For example, in the case of a copolymer composed of two types of monomers, the glass transition temperature can be theoretically calculated based on the Tg (θ1, θ2) of the homopolymer of each copolymerization monomer A and B and the composition ratio of each copolymerization monomer (C1, C2) using the following Fox formula. 1 / θ=c1 / θ1+c2 / θ2 In other words, the glass transition temperature of a copolymer of a vinyl ether having an alkyl group in its skeleton (monomer A) and a vinyl ether having a cyclic hydrocarbon (monomer B) can be calculated from the Tg(A) of the homopolymer of monomer A, the Tg(B) of the homopolymer of monomer B, and the composition ratio of monomer A and monomer B.

[0016] For example, as shown in Figure 1, the Tg of the copolymer obtained by copolymerizing poly(n-butyl vinyl ether) (poly(NBVE); Tg = -56°C) and poly(tricyclodecane vinyl ether) (poly(TCDVE); Tg = 105°C) is controlled by the TCDVE fraction (or NBVE fraction) according to the Fox formula. It has been reported that this is possible (Non-Patent Document 1). In Fig. 1, black circles (●) indicate theoretical values ​​of Tg calculated from the mole fraction, and white circles (○) indicate theoretical values ​​of Tg calculated from the mass fraction. According to this formula, when NBVE:TCDVE=5.8:4.2-7.2:2.8 (molar ratio), the theoretical Tg of the copolymer is in the range of -10.2°C to 12.5°C. In addition, in the copolymer of poly(n-decyl vinyl ether) (NDVE); raw material monomer with Tg=-62°C, and poly(tricyclodecane vinyl ether) (poly(TCDVE); raw material monomer with Tg=105°C), the theoretical Tg is -33.0°C to -15.1°C when NDVE:TCDVE=5.8:4.2-7.2:2.8.

[0017] On the other hand, although Tg is an index showing that the coating layer has transitioned to a state where it can be peeled off from the seed, it is not a temperature that indicates the fluidity of the polymer, and the softening temperature is a more direct index showing that the coating layer will peel off from the seed at a certain temperature. Furthermore, Tg and the softening temperature do not necessarily correlate. Differential scanning calorimetry (DSC) or TMA can be used to measure Tg.

[0018] (Type of polymer) The polymer used as the coating material in the present invention is a so-called hydrophobic polymer, and is not particularly limited as long as it prevents the seeds from absorbing water due to the penetration of water into the layer made of the polymer when the seed is coated and solidified (polymer layer), and has a certain viscosity (fluidity) when the polymer layer softens at a predetermined temperature, thereby allowing it to be peeled off from the coated seed. As described above, the "hydrophobic polymer" refers to a polymer with low affinity for water, and examples of the polymer include polymers having a hydrophobic structure. Examples of the hydrophobic structure include non-polar groups, non-polar skeletons, and the like, and in particular, hydrocarbon groups, cyclic hydrocarbon groups, and hydrocarbon main chains. In addition, copolymers having a monomer (hydrophobic monomer) having a hydrophobic structure as a constituent unit can also be included in the hydrophobic polymer.

[0019] (Hydrophobic polymer) As a hydrophobic polymer having the above properties, a vinyl ether copolymer consisting of two kinds of repeating units represented by the following general formula (1) can be used. In the formula, p is 2 to 95, q is 2 to 38, and m is the number of alkylene groups and represents an integer of 0 to 1 (i.e., a single bond or a methylene group). Furthermore, p and q satisfy p:q=5.8:4.2-7.2:2.8, and can preferably be in the range of p:q=6:4-7:3. [ka]

[0020] R1 in the general formula (1) is an alkyl group having 3 to 10 carbon atoms, and specifically can represent a linear alkyl group such as an n-propyl group, an n-butyl group, an n-pentyl group, an n-hexyl group, an n-heptyl group, an n-octyl group, an n-nonyl group, or an n-decyl group, as well as a branched alkyl group such as an isopropyl group, an isobutyl group, a t-butyl group, an isopentyl group, a neopentyl group, an isohexyl group, an isoheptyl group, an isooctyl group, a 2-ethylhexyl group, an isononyl group, or an isodecyl group.

[0021] R2 in the general formula (1) is not particularly limited as long as it is a cyclic hydrocarbon group having an alicyclic group having 10 to 15 carbon atoms as a basic skeleton, and is preferably a tricyclo[5.2.1.0] group represented by the following formula (2). 2,6 ]decyl group, tricyclodecenyl group represented by formula (3) or formula (4), and pentacyclopentadecyl group represented by formula (5) or formula (6) can be preferably used. In each formula, * represents a bond. [ka]

[0022] The vinyl ether copolymer can be produced by polymerizing a vinyl ether having the above-mentioned R1 (alkyl group) (monomer A) and a vinyl ether having R2 (alicyclic group) (monomer B) in a solvent. As one embodiment of the polymerization method, for example, living cationic polymerization is adopted, in which polymerization is carried out in an aromatic hydrocarbon solvent such as toluene or xylene, or a halogenated hydrocarbon such as methylene chloride, which dissolves each monomer and polymer. Living cationic polymerization is useful as a method for obtaining a polymer with a narrow molecular weight distribution, since it is possible to easily control the degree of polymerization. This makes it possible to control the molecular weight of the copolymer, and to easily adjust the viscosity of the coating material. In addition, commonly used polymerization methods such as anionic polymerization, living anionic polymerization, cationic polymerization, free radical polymerization, and living radical polymerization can be used.

[0023] Monomer A is not particularly limited as long as it is a vinyl ether having an alkyl group having 3 to 10 carbon atoms. Examples of the monomer A include vinyl ethers having a linear alkyl group such as n-propyl vinyl ether, n-butyl vinyl ether, n-pentyl vinyl ether, n-hexyl vinyl ether, n-heptyl vinyl ether, n-octyl vinyl ether, n-nonyl vinyl ether, and n-decyl vinyl ether, as well as vinyl ethers having a branched alkyl group such as isopropyl vinyl ether, isobutyl vinyl ether, t-butyl vinyl ether, isopentyl vinyl ether, neopentyl vinyl ether, isohexyl vinyl ether, isoheptyl vinyl ether, isooctyl vinyl ether, 2-ethylhexyl vinyl ether, isononyl vinyl ether, and isodecyl vinyl ether.

[0024] Monomer B is not particularly limited as long as it is a vinyl ether having a cyclic hydrocarbon group with an alicyclic group as the basic skeleton. For example, 8-tricyclo[5.2.1.0 2,6 ]decane vinyl ether (formula (2-1)), 8-tricyclo[5.2.1.0 2,6 ]Decane monomethyl vinyl Examples of the vinyl ether include 8-tricyclodecene vinyl ether (formula (2-2)), 8-tricyclodecene vinyl ether (formula (3-1), formula (3-2)), 8-tricyclodecene monomethyl vinyl ether, 8-pentacyclopentadecane vinyl ether (formula (5-1), formula (6-1)), 8-pentacyclopentadecane monomethyl vinyl ether (formula (5-2), formula (6-2)), 8-pentacyclopentadecane vinyl ether, and 8-pentacyclopentadecane vinyl ether tricyclodecene monomethyl vinyl ether. These vinyl ethers can be synthesized based on the method described in Japanese Patent No. 4136886. [ka]

[0025] (coated seeds) The seeds used in the present invention are not particularly limited, and examples thereof include seeds of vegetables, flowers, pasture plants, grains, industrial crops, trees, etc., and more specifically, the following seeds are included: Examples of vegetable seeds include seeds of the Cucurbitaceae family, such as cucumber, melon, pumpkin, etc.; seeds of the Solanaceae family, such as eggplant, tomato, etc.; seeds of the Fabaceae family, such as pea, kidney bean, etc.; seeds of the Liliaceae family, such as onion, leek, etc.; seeds of the Brassica family, such as turnip, Chinese cabbage, cabbage, broccoli, cauliflower, etc., and seeds of the Brassicaceae family, such as radish, seeds of the Apiaceae family, such as carrot, celery, etc.; seeds of the Asteraceae family, such as burdock, lettuce, garland chrysanthemum, etc.; seeds of the Lamiaceae family, such as perilla, etc.; and seeds of the Amaranthaceae family, such as spinach, etc. Examples of flowering plant seeds include seeds of the Brassicaceae family, such as snapdragon, stock, and alyssum; seeds of the Campanulaceae family, such as lobelia; seeds of the Asteraceae family, such as aster, zinnia, and sunflower; seeds of the Ranunculaceae family, such as delphinium; seeds of the Scrophulariaceae family, such as snapdragon; seeds of the Primula family, such as primula; seeds of the Begonia family, such as begonia; seeds of the Lamiaceae family, such as salvia; seeds of the Viola family, such as pansy and viola; seeds of the Solanaceae family, such as petunia; and seeds of the Gentianaceae family, such as eustoma. Examples of pasture grass seeds include seeds of timothy (Phleum pratense), Italian ryegrass (Ryegrass), Bermuda grass (Cynostemma dactylon), oat hay, sudan grass, crane grass, fescue, and orchard grass (Dactylon grass). Examples of cereal seeds include rice, barley, wheat, soybean, foxtail millet, buckwheat, barnyard millet and millet. Examples of seeds of industrial crops include seeds of the Amaranthaceae family, such as sugar beet, seeds of the Solanaceae family, such as tobacco, seeds of the Brassicaceae family, such as rapeseed, and seeds of the Gramineae family, such as rush. Examples of tree seeds include seeds of azalea, oak, cedar, cypress, Japanese oak, beech, pine, and azalea.

[0026] The method for producing the coated seed of the present invention is not particularly limited, and for example, a known device such as a granulator can be used. Specifically, the seeds are fluidized using a fluidizer or a jet device, or the seeds are brought into a rolling state using a rolling device such as a rotating pan or a rotating drum, and a molten liquid or solution of the coating material (vinyl ether-based copolymer) according to the present invention is added to the seeds by dropping, spraying, or the like to coat the surfaces of the seeds.

[0027] The sowing method of the coated seeds of the present invention is not particularly limited, so long as the seeds are sowed at a temperature lower than the softening temperature of the coating material, preferably lower than the Tg, from the viewpoint of obtaining the effects of the present invention, i.e., from the viewpoint of preventing the coating material from peeling off from the seeds during sowing. For example, there are a method of only sowing the seeds on the soil surface, a method of sowing the seeds on the soil surface and then covering with soil, a method of sowing the seeds on the soil surface and then mixing with soil, a method of sowing the seeds in a seedling pot such as a paper tube filled with soil and then covering with soil, etc. The type of soil is also not particularly limited, so long as it is a type that is generally applicable to the above-mentioned seeds. EXAMPLES

[0028] The present invention will be described more specifically below with reference to examples, but the present invention is not limited to these examples and comparative examples.

[0029] [Production Example 1] Preparation of seed coating polymer In order to prepare polymers with different viscosities, copolymers with four different molecular weights, target molecular weights of 1,000, 5,000, 10,000, and over 10,000, were prepared according to the following procedure. In addition, based on the relationship between the TCDVE fraction and Tg shown in Figure 1, two types of copolymer compositions were determined, with molar ratios of NBVE (n-butyl vinyl ether):TCDVE (tricyclodecane vinyl ether) = 6:4 and 7:3, so that the Tg of the copolymer would be 5 to 10°C, and various copolymers shown in Table 1 were prepared according to the following procedure. A homopolymer of TCDVE was also prepared.

[0030] <Polymer Preparation Method> n-Butyl vinyl ether (NBVE, liquid monomer, FUJIFILM Wako Pure Chemical Industries, Ltd.), tricyclodecane vinyl ether (TCDVE, liquid monomer, Maruzen Petrochemical Co., Ltd.), boron trifluoride diethyl etherate (BF3OEt2 (liquid)), and hydrogen chloride solution (HCl; Aldrich, 4.0 M 1,4-dioxane solution) were each dispensed into ampoules, stored in a refrigerator, and used in the following production. Furthermore, zinc chloride solution (ZnCl2; Aldrich, 1.0 M diethyl ether solution), diethyl ether ((C2H5)2O, FUJIFILM Wako Pure Chemical Industries, Ltd., ultra-dehydrated), and toluene (C6H5CH3, FUJIFILM Wako Pure Chemical Industries, Ltd., ultra-dehydrated) were each commercially available products, and water was removed and purified using an organic solvent purification apparatus before being used in the following production.

[0031] A three-way cock-fitted eggplant-shaped flask was baked with a heating gun while nitrogen was flowing in it to prepare for an anhydrous reaction system. The liquid monomer, initiator (solution), and activator solution described below were added to this flask to achieve the specified concentrations, and the reaction was carried out. Specifically, a recovery flask containing liquid monomers (13.5 ml) in a predetermined molar ratio shown in Table 1 was cooled to -30°C, and then an initiator (BF3OEt2 / 1.5 ml) was added to prepare a polymerization solution (Production Method A). Alternatively, an initiator solution (HCl solution / 1.5 ml) and an activator solution (ZnCl2 solution / 1.5 ml) were added in this order to liquid monomer (12.0 ml) having a predetermined molar ratio shown in Table 1 to prepare a polymerization solution (Production Method B). After carrying out the polymerization in this manner on a scale of 15 ml of polymerization solution, the polymerization was terminated by adding 2 mL of water containing a small amount of aqueous ammonia. The resulting polymer was then dissolved in a small amount of THF and added to a large amount (~800 ml) of methanol for reprecipitation to purify the polymer, yielding the desired polymer (coating material). The molecular weight, glass transition temperature and softening temperature of the resulting polymer were measured according to the following procedures.

[0032] (Test Example 1) Measurement of molecular weight of polymer The number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of the obtained polymer were calculated using gel permeation chromatography (GPC) with a calibration curve prepared from standard polystyrene (molecular weights: 96,400, 37,900, 18,100, 9,100, 5,870, 2,670, 1,050, 500). Gel Permeation Chromatography (GPC) Pump: HITACHI l-7100 Differential refractometer: TOSOH RI-8020 UV-visible spectrometer: SHIMADZU SPD-10a Columns: Shodex LF-802, Shodex LF-804 (3 columns) Solvent: THF Flow rate: 1.0ml / min (40.0℃)

[0033] (Test Example 2) Measurement of glass transition temperature (Tg) of polymer The glass transition temperature (Tg) of the obtained polymer was determined by differential scanning calorimetry (DSC). A SHIMADZU DSC-60 was used as the apparatus, and measurements were performed under a nitrogen atmosphere using an aluminum sample pan. The first heating and cooling rates were 10°C / min, and the second heating and cooling rates were 5°C / min. Data from the midpoint of the second heating was used for analysis.

[0034] (Test Example 3) Measurement of polymer softening temperature The obtained polymer was filled into a crimp cell (aluminum pan φ5.8 mm × height 1.5 mm) for DSC measurement, and the cell was leveled to the top edge. The polymer that was liquid when filled was left as it was, and the polymer that was solid or had a high viscosity when filled was heated to about 60 ° C and then filled into the crimp cell. This was placed on a temperature control unit (TOB-1000, Hayashi Repic Co., Ltd.) set at -20 ° C, and a roughly Y-shaped stainless steel rod weighing 0.21 g was inserted into the center of the polymer so that it was in contact with the bottom of the cell and stood upright, with the Y facing upward (see Figure 2). The roughly Y-shaped stainless steel rod had an overall length of 2.1 cm, a handle length of 0.9 cm, a bottom surface of the handle: 1.0 mm × 0.7 mm (approximately rectangular), a length from the crotch of the branched part to the top surface of the branched part of 1.2 cm, a thickness of the branched part of 0.7 mm, and a distance between the top surfaces of the branched parts of 0.85 cm. The temperature of the temperature control unit is gradually increased from -20°C, and the stainless steel rod At the moment when the stainless steel rod was completely tilted and in contact with the polymer, the surface temperature of the polymer in the aluminum pan was measured with an infrared radiation thermometer (SK-8900, Sato Keiryoki Seisakusho Co., Ltd.) and this was taken as the softening temperature.

[0035] The results of measuring the molecular weight (number average molecular weight, molecular weight distribution), glass transition temperature, and softening temperature of the obtained polymer are shown in Table 1. The target number average molecular weight (Calc(Mn)) and the theoretical glass transition temperature (Calc(Tg)) calculated by the Fox formula are also shown in Table 1.

[0036] [Table 1]

[0037] As shown in Table 1, the number average molecular weights (Mn) of the prepared polymers were all high relative to the calculated values, but the molecular weight distributions (Mw / Mn) of the prepared polymers were narrow, ranging from 1.08 to 1.22, confirming that living polymerization was proceeding. As shown in Table 1, both Tg (measured value) and softening temperature showed a tendency to decrease as the TCDVE fraction decreased, similar to the theoretical values. Furthermore, for copolymers, the measured Tg values ​​were all lower than the theoretical Tg values ​​calculated by the Fox formula. Furthermore, for copolymers with the same composition, the values ​​of Tg (measured value) and softening temperature changed depending on the molecular weight.

[0038] [Production Example 2] Preparation of coated seeds Each polymer obtained in [Production Example 1] was placed in a sample bottle at room temperature, and uncoated seeds (sugar beet seeds or onion seeds) were added thereto, stirred with a medicine spoon, and the seeds were removed. The removed seeds were left at a low temperature (-20°C) to harden the polymer, and coated seeds were obtained. The polymer (NBVE and TCVE molar ratio 6:4, Mn = 18,700) that was difficult to coat onto seeds due to its high molecular weight and high viscosity, and poly(TCDVE) with a high Tg, were first dissolved in dichloromethane (CH2Cl2) to adjust the viscosity before being used to coat the seeds. Using the obtained coated seeds, a coating peeling test and a germination test were carried out according to the following procedures.

[0039] (Test Example 4) Coating peeling test Seeds coated with each polymer were placed on a petri dish and left in an incubator (KMH-207, AS ONE Corporation) at 5°C for 10 days, then the incubator was cooled to 10°C and left for 3 days. The temperature inside the incubator was then lowered to 20°C, and the peeling of the coating from the seeds was visually confirmed. Observation was started at 5°C and continued for 9 days at 20°C. If the coating had peeled off even partially from the seeds, it was rated as ◯, and if the coating had remained completely without peeling, it was rated as ×. The results are shown in Table 2. In addition, the peeling status before the start of observation and 16 days after the start of observation (4 days after the temperature was increased to 20°C) is shown in Figure 3(A) for seeds (sugar beet seeds) coated with a copolymer of Mn = 1,700 in a composition ratio of NBVE:TCDVE = 6:4, and in Figure 3(B) for seeds (sugar beet seeds) coated with a copolymer of Mn = 18,700.

[0040] [Table 2]

[0041] As shown in FIG. 3, when comparing copolymers with a composition ratio of 6:4 by molecular weight, the copolymer with Mn=1,700 was confirmed to have completely peeled off 16 days after the start of observation, that is, 4 days after the temperature was increased to 20°C (FIG. 3(A)). However, the copolymer with Mn=18,700 could not be confirmed to have peeled off even after the temperature was increased to 20°C, that is, 16 days after the start of observation (4 days after the temperature was increased to 20°C) (FIG. 3(B)), and the copolymer could not be confirmed to have peeled off even after 32 days (20 days after the temperature was increased to 20°C) or more after the start of observation. Although the difference in Tg between these two copolymers is about 3°C, and even in an environment of 20°C, which is significantly higher than the Tg of these copolymers, the copolymer with Mn=18,700 did not peel off from the seeds. One of the reasons for this result is that the high molecular weight polymer is highly viscous and therefore difficult to peel off, making it unsuitable for the seed coating material of the present invention. However, Tg is the temperature indicating the freezing / releasing of the micro-Brownian motion of the polymer main chain, and Tg itself cannot be said to be the fluidity of the polymer or a temperature that serves as an index thereof. In the present invention, the softening temperature, defined as the temperature at which a solidified polymer has fluidity and becomes liquid, can be used as an index of the fluidity of the polymer. As shown in Table 2, the softening temperatures of the copolymer with Mn=1,700 and the copolymer with Mn=18,700, with a composition ratio of 6:4, were 8.2°C and 21.0°C, respectively, and while the difference in Tg was 3.2°C, the difference in softening temperature was 12.8°C, resulting in a large difference. This peeling test was carried out under conditions below the softening temperature (21°C) of the copolymer with Mn=18,700, so it is believed that the copolymer did not peel off from the seeds. These results show that a required characteristic of the coating material is that the peeling temperature must exceed the softening temperature due to the viscosity specific to polymers. In other words, it appears desirable to set the softening temperature of the coating material lower than the anticipated optimum temperature for seed germination.

[0042] (Test Example 5) Germination test The germination test was carried out according to the schedule (1) to (3) shown in Figure 4. The soil used for raising the seedlings was a general seedling raising soil that did not contain a solidifying agent. <Non-coated seeds> (1) Seeds that were not polymer-coated were soaked in water and grown in the above soil in an incubator set at 3°C ​​or at room temperature, and germination was confirmed (see Figure 4: Schedule (1)). <Coated seeds> (2) The polymer-coated seeds were sown in the soil and then grown in an incubator while the temperature was raised according to a schedule of 8 days at 3°C, 4 days at 10°C, and 1 to 7 days at 20°C, and germination was confirmed (see Figure 4: Schedule (2)). (3) The pots in which the polymer-coated seeds were sown in the soil were immersed in water, and seedlings were grown under the same schedule as in (2) (8 days at 3°C ​​→ 4 days at 10°C → 1 to 7 days at 20°C) while constantly absorbing water. For samples that did not germinate even after the period during which germination was confirmed at 20°C in schedule (2), the pots were removed from the water to remove the immersion, and seedlings were grown for another 4 to 8 days at 20°C, and germination was confirmed (see Figure 4: schedule (3)).

[0043] In a germination test according to schedule (1) conducted using uncoated seeds, germination was confirmed six days after sowing at 3°C. When seeds were sown at room temperature, they germinated three days later. The germination rate was 100% under all conditions. These results also confirmed that the seeds' germination function was not lost even when soaked in water and exposed to low temperatures.

[0044] In a germination test using coated seeds and carried out according to schedule (2), germination was confirmed in seeds coated with a copolymer of NBVE and TCVE with a molar ratio of 6:4 and Mn = 1,700 within one day (13 days after sowing) after the temperature had been raised to 20°C at the earliest. As shown in Table 3, the germination rate of seeds coated with a copolymer of Mn = 1,700 was 50%, which was lower than that of schedule (1) (germination rate: 100%), but it was confirmed that polymer coating makes it possible to germinate seeds without killing them (see Figure 5 (sugar beet seeds)).

[0045] In addition, in a germination test conducted using a sample of the same composition molar ratio and molecular weight according to schedule (3), the sample did not germinate even after the germination period for schedule (2), but germination was confirmed four days after the water was removed. The temperature conditions for schedule (3) (with water soaking) and schedule (2) (without water soaking) were the same, and the seeds germinated after the water soaking was removed and they were grown in normal seedling conditions. This suggests that even in an environment above the softening temperature of the coating material, the presence of water around the seeds prevented the hydrophobic coating material from peeling off from the seeds, completely inhibiting the seeds from absorbing water, thereby suppressing germination.

[0046] In addition, because the final temperature (germination temperature) for Schedules (2) and (3) was set to 20°C, it was predicted that seeds coated with copolymers (NBVE:TCDVE (molar ratio) = 6:4, Mn = 18,700) and poly(TCDVE), which have softening temperatures above 20°C, would not germinate because the coating would not peel off. However, as shown in Table 3, germination was confirmed with these coating materials. Regarding this result, when the soil was checked after germination, it was confirmed that the poly(TCDVE) coating had cracked and remained in a shell-like state (see Figure 6, which shows the results for coated seeds made from sugar beet seeds).From this, it is believed that the cause of germination was that dichloromethane (CH2Cl2), which was used to adjust the viscosity when coating the seeds, evaporated when the coating solidified, causing voids in the coating, which allowed the seeds to absorb water through these voids, cracking the coating material and germinating.

[0047] [Table 3]

[0048] (Test Example 6) Peeling test and germination test using recoated coated seeds Coated seeds (2) with a thicker coating layer were produced by repeatedly applying and drying the poly(TCDVE) coated seeds used in Test Example 5. Using these coated seeds (2), the temperature inside the incubator was set to 20°C from the first day, and peeling tests and germination tests were carried out. Coated seeds (2), which were coated again with poly(TCDVE) [molecular weight 41,200], did not germinate, and no peeling of the coating material was observed. This result supports the conclusion that the cause of germination, as shown in Table 3, was due to the generation of voids during drying. Similarly, no germination was observed when the temperature inside the incubator was raised to 25°C.

[0049] (Test Example 7) Test showing correlation between polymer viscosity and peeling In order to show the correlation between the viscosity of the polymer and its peeling from the seed, the obtained polymer was used to coat the seeds and the peeling of the polymer from the seeds was examined. Preparation of the seed coating polymer (Preparation A), measurement of the molecular weight of the polymer, measurement of the softening temperature, preparation of the coated seeds, and coating peeling test were carried out according to the procedures described above. The viscosity of the polymer was measured at 25°C using a vibration viscometer (Seconic Corp., VM-10A-H model). The results are shown in Table 4. Peeling of the coating layer was confirmed at least at viscosities of 52 to 184 Pa·S.

[0050] [Table 4]

[0051] From the above results, it was confirmed that, when designing coated seeds according to the present invention, it is desirable to design the coating material so that the temperature at which the coating material peels off from the seed exceeds the softening temperature of the coating material (the softening temperature of the coating material is set lower than the anticipated optimum temperature for seed germination), and that high molecular weight polymers are not suitable as coating materials because they tend to have high viscosity and high softening temperatures. In addition, in a copolymer with NBVE:TCDVE (molar ratio) = 6:4, the difference in softening temperature between the polymer with the target molecular weight: Mn = 1,000 and the polymer with Mn = 5,000 is not so great. However, it was confirmed that the polymer had a lower molecular weight than the 6:4 and 7:3 compositions, and therefore, when the softening temperatures are approximately the same, it is preferable to use a polymer with a lower molecular weight.

Claims

1. A coated seed having a coating layer containing a vinyl ether copolymer on a surface of the seed, The vinyl ether copolymer is characterized in that it has a softening temperature of 0.5°C or higher and a Tg of -35°C to 13°C, as defined by the following conditions: Coated seeds. <Softening temperature> The vinyl ether copolymer was filled into an aluminum pan (φ5.8 mm × height 1.5 mm), A roughly Y-shaped stainless steel rod (weight 0.21 g, total length of stainless steel rod 2.1 cm, length of handle 0.9 cm, bottom of handle: 1.0 mm x 0.7 mm (roughly rectangular), length from crotch of branch to top of branch 1.2 cm, thickness of branch 0.7 mm, distance between tops of branch 0.85 cm) having a cylindrical handle and a branch at its tip that spreads out in two directions and has a flat top surface was inserted into the center of the copolymer with the branch facing upward, and the stainless steel rod was placed in contact with the bottom of the aluminum pan, and the temperature was raised from -20°C. The surface temperature of the copolymer measured with an infrared thermometer at the moment when the stainless steel rod falls completely is taken as the softening temperature.

2. The vinyl ether copolymer has a viscosity of 30 to 300 Pa·s at 25°C and a number average molecular weight of 800 to 15,000. The coated seed according to claim 1.

3. The coated seed according to claim 2 , wherein the vinyl ether copolymer has a molecular weight distribution (Mn / Mw) of 2.0 or less.

4. The coated seed according to claim 1 , wherein the vinyl ether copolymer comprises a repeating unit represented by the following formula (1): 【Chemistry 1】 (In formula (1), R 1 represents an alkyl group having 3 to 10 carbon atoms, R 2 represents a cyclic hydrocarbon group having an alicyclic group having 10 to 15 carbon atoms as a basic skeleton, p represents an integer of 3 to 95, q represents an integer of 2 to 38, and p and q satisfy the relationship p:q=5.8:4.2-7.2:2.8; m is the number of alkylene groups and is an integer of 0 or 1.

5. The R 1 is the group consisting of n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, isopropyl, isobutyl, t-butyl, isopentyl, neopentyl, isohexyl, isoheptyl, isooctyl, 2-ethylhexyl, isononyl, and isodecyl groups. is one or more groups selected from The R 2 is one or more groups selected from the group consisting of groups represented by the following formulas (2) to (6): The coated seed according to claim 4. 【Chemistry 2】 (In the formula, * represents a bond.)

Citation Information

Patent Citations

  • Coated paddy rice seed

    JP1979097209A

  • JP1981501600A

  • Seed coating

    JP1991198703A

  • Seed-coating composition for low temperature application

    JP2001120012A

  • slow release nitrogen seed coat

    JP2005520564A

Cited By

  • Control device

    CN122431059A

  • A method for cultivating plants and a coated body using multiple polymer layers.

    JP7881135B1

  • Body coated by multi-layer polymer, and method for cultivating plant

    WO2026141387A1